2013
DOI: 10.4103/0301-4738.99996
|View full text |Cite
|
Sign up to set email alerts
|

Spectacle compliance amongst rural secondary school children in Pune district, India

Abstract: Background:Refractive errors (RE) are the most common cause of avoidable visual impairment in children. But benefits of visual aids, which are means for correcting RE, depend on the compliance of visual aids by end users.Aim:To study the compliance of spectacle wear among rural school children in Pune district as part of the sarva siksha abhiyan (education for all scheme) after 6 - 12 months of providing free spectacles.Settings and Design:Cross-sectional follow-up study of rural secondary school children in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
116
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(136 citation statements)
references
References 12 publications
16
116
4
Order By: Relevance
“…3,6,7,[23][24][25] Observed rates of wear were low, ranging from 13% to 41%. 3,6,7,21,23,24 All of the few studies reporting higher rates (46% by Keay and associates in China, 25 56% by Vincent and associates in Thai refugee camps, 22 and 58% by von-Bischhoffshaussen and associates in Chile 20 ) relied on self-report and/or estimates of teachers or parents, 20,22 and had low (58%-76%) rates of follow-up 20,22 or assessment times as short as 1 month after spectacle distribution. 25 It would appear that longer-term (over the course of a school year) compliance with free spectacles, as measured by objective indicators such as observed wear at unannounced examinations, is low among children without additional interventions.…”
Section: Whereas Previous Studies Of Programs Providingmentioning
confidence: 99%
“…3,6,7,[23][24][25] Observed rates of wear were low, ranging from 13% to 41%. 3,6,7,21,23,24 All of the few studies reporting higher rates (46% by Keay and associates in China, 25 56% by Vincent and associates in Thai refugee camps, 22 and 58% by von-Bischhoffshaussen and associates in Chile 20 ) relied on self-report and/or estimates of teachers or parents, 20,22 and had low (58%-76%) rates of follow-up 20,22 or assessment times as short as 1 month after spectacle distribution. 25 It would appear that longer-term (over the course of a school year) compliance with free spectacles, as measured by objective indicators such as observed wear at unannounced examinations, is low among children without additional interventions.…”
Section: Whereas Previous Studies Of Programs Providingmentioning
confidence: 99%
“…As many as 13 million worldwide, have uncorrected refractive error, numerous programs have attempted to address the problem of uncorrected refractive error through school-based vision testing and spectacle distribution programs. Unfortunately, most programs have found that at follow up, the majority of children provided spectacles at no charge were not wearing them or non compliant on wearing refractive correction (5,7,(13)(14)(15)21) Reasons for non-compliance vary by study and population, most common reasons were lost or broken eyeglasses, concern about appearance or teasing, worry that the eyeglasses will make the eyes worse, eyeglasses kept at home or used only for special occasions (1-7, 16, 21) .…”
Section: Introductionmentioning
confidence: 99%
“…The dictionary (The Oxford Concise Dictionary) meaning of compliance refers to "Obedience to a request or command", in respect to our study, we used to prescribe for spectacles but it is useful only at time when child patients are wearing them. Refractive errors are commonly found as the causative agent for visual impairment in the most surveyed population and this impairment is easily treatable (1)(2)(3)(4)(5)(6)(7) . Previous studies shows prevalence of refractive error differs with geographic location, age, gender, education level, and amount of near work (1)(2)(3)(4)(5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations